2021
DOI: 10.18240/ijo.2021.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Similar therapeutic effects of 125I seed radiotherapy and γ-ray radiotherapy on lacrimal gland adenoid cystic carcinoma

Abstract: AIM: To evaluate the survival outcomes of patients with lacrimal gland adenoid cystic carcinoma who underwent eye-sparing surgery combined with 125I seed implantation radiotherapy or local external γ-ray radiotherapy. METHODS: In this retrospective comparative case series, the clinical records of 27 primary and 8 recurrent patients were reviewed. Univariate and multivariate analyses were used to identify risk factors associated with distant metastasis (DM), and the overall survival (OS) after the initial surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Li et al [45] found that there was no significant difference in local control, control of metastasis to regional lymph nodes, or control of distant metastasis between the IR and ERBT groups. In the retrospective comparison case series, the clinical records of 27 patients with primary LGACC and 8 patients with recurrent LGACC were compared, and no statistically significant difference was found in the efficacies of IR and ERBT in terms of distant metastasis rates [16] . Previous studies have reported distant metastasis rates of 11%-56% and external radiation rates of 11%-67% for IR [7,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [45] found that there was no significant difference in local control, control of metastasis to regional lymph nodes, or control of distant metastasis between the IR and ERBT groups. In the retrospective comparison case series, the clinical records of 27 patients with primary LGACC and 8 patients with recurrent LGACC were compared, and no statistically significant difference was found in the efficacies of IR and ERBT in terms of distant metastasis rates [16] . Previous studies have reported distant metastasis rates of 11%-56% and external radiation rates of 11%-67% for IR [7,17] .…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 16 Surgical resection combined with radiotherapy/chemotherapy, including 125 I implanted internal radiotherapy, local external radiotherapy, or transarterial interventional chemotherapy, is the most common approach used to treat patients with LGACC. 17 However, the clinical outcomes of these treatments are far from satisfactory. In recent years, targeted therapy has become a new strategy for cancer treatment, including targeted therapy for LGACC.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The main mechanism of action for the use of 125 I is to place it at the tumor site and kill tumor cells directly using gamma rays (0.03548 MeV) released from its decay process, thereby partially or completely eliminating the lesions and avoiding the recurrence or distant metastasis. 11 In addition, 125 I can also serve as an imaging probe for nanocarriers (NCs), 12,13 tyrosine, and proteins 14,15 in theragnostics and drug tracing. 125 I labeling on the surface of NCs or proteins is well suited for the study of its physiological roles and metabolism due to its short half-life of 60.14 days.…”
Section: Introductionmentioning
confidence: 99%